Dietary fibers as potential partial meat substitutes in the technological quality of a fish burger (Research, Society and Development, 2022)
Fish hamburgers have significant water exudation after freezing and thawing, accompanied by grilling. The application of white dietary fibers, due to high hydration capacity and without dramatically changing the product's color, may overcome unwanted effects of the application of fish meat in hamburgers. So, this study aimed to incorporate mixed resistant starch, carboxymethylcellulose and white wheat fiber in fish hamburgers and evaluate the final product's technical performance. The study was conducted by a Simplex-Centroid Mixture Design, and the dependent variables were assessed through the Response Surface Methodology (P < 0.10 and R2 > 0.75). The optimal point was achieved by the combination of dietary fibers in the proportion of mixed resistant starch (1.10 %), carboxymethylcellulose (2.92 %) and white wheat fiber (0.64 %), with desirability of 84.19 %. By comparing the results obtained for the optimized point and the standard sample, the main advantages observed were the 24.17 % increase in water retention capacity, a 52.05 % decrease in cooking weight loss and an instrumental texture with values better in technological performance. In this way, the hamburgers were softer and more succulent, without significant changes in water activity. In addition, the optimal point presented lighter colors and more oversized reddish and yellowish shades. Therefore, adding dietary fibers with an adequate balance between soluble and insoluble fractions resulted in satisfactory technological performance in fish hamburgers.